Ripening and postharvest quality of guavas treated with plant regulators - Alex Sanches; Elem Maria Feitosa (Journal of Horticulture and Postharvest Research)
Purpose: Guava is a tropical and subtropical fruit recognized for its nutritional quality. However, o it is a climacteric fruit, that is, with high respiratory activity and ethylene production during ripening, it becomes extremely perishable under environmental conditions, requiring conservation technologies that allow its commercialization without compromising post-harvest quality during storage. Therefore, the objective of this study was to evaluate the effect of plant regulators (gibberellic acid – GA3 and ethephon) on ripening and quality preservation during storage at room temperature. Research method: Physiologically mature guavas (stage 3) were harvested in a commercial orchard, selected and sanitized in a chlorinated solution, and immersed in the following solutions: distilled water (control), GA3, and ethephon (150 mg.L-1) for a period of 10 minutes and subsequently stored under room temperature conditions (28 ± 2 ºC) for 12 days with physical-chemical quality assessments carried out every three days. Findings: Treatment with GA3 provided lower values ​​of mass loss, soluble solids, titratable acidity, and total sugars, in addition to higher values ​​of firmness and vitamin C of the fruits analyzed, while the opposite effect was observed in guavas treated with ethephon. In general, the postharvest application of GA3 delays ripening, making it possible to extend marketing for up to 9 days, on the other hand, ethephon anticipates ripening, making them fully ripe after 6 days of storage. Research limitations: There were no limitations to carrying out this research. Originality/Value: This research's results support staggering the ripening of guava over time, allowing the fruit's commercialization period to be extended.